Effects of blood flow restriction on cerebral blood flow during a single arm-curl resistance exercise - Morita, T.; Yumoto, M.; Fukuda, T.; Sato, Y.; Ikeda, K.; Kikuchi, H. (International Journal of KAATSU Training Research, 2010)
Low-intensity resistance exercise with blood flow restriction (BFR), also known as "Kaatsu," causes a dramatic increase in the secretion of growth hormone. Several reports have shown that Kaatsu is effective for training in patients with stroke. However, the influence of Kaatsu training on brain function remains unclear. This study aimed to investigate the acute effects of Kaatsu training on blood flow in the brain. Six healthy male subjects performed a single-arm curl with and without BFR using 20% of the weight of 1 repetition maximum(RM); 1 set of 30 repetitions (reps) was followed by 3 sets of 15 reps, with a 30-s interval in between. During the procedure, cerebral blood flow was measured using near-infrared spectroscopy (NIRS). During arm curls with BFR, the oxygenated hemoglobin (oxy-Hb) concentration of the contralateral motor cortex increased significantly compared to that during curls without BFR. The results of this study suggest that Kaatsu training has a positive effect on the brain by increasing cerebral blood flow and that it is useful for treating diseases such as stroke and cognitive disorders caused by brain dysfunction.